PENGARUH JUMLAH PENGANGGURAN DAN JUMLAH PENDUDUK MISKIN TERHADAP INDEKS PEMBANGUNAN MANUSIA - Hendri Andika Saputra; Irsad Lubis (Bisnis-Net, 2023)
This text discusses a research study conducted in Bahasa Indonesia. It seems to be focused on examining the influence of unemployment and the number of poor people on the Human Development Index in the city of Bukittinggi. The data used in the study is secondary data obtained from the Central Statistics Agency of Bukittinggi. The data analysis technique employed is multiple regression analysis using the Eviews 12 program.The results of the analysis indicate that the variable of unemployment has a positive and significant effect on the Human Development Index in Bukittinggi, as evidenced by the t-value of 3.068 with a significance level (Sig.) smaller than the significance level (0.0107 < 0.05). On the other hand, the variable of the number of poor people shows a negative and significant impact on the Human Development Index in Bukittinggi, with a t-value of -3.788 and a significance level (Sig.) smaller than the significance level (0.003 < 0.05).In summary, the study suggests that unemployment has a positive and significant influence, while the number of poor people has a negative and significant influence on the Human Development Index in Bukittinggi.